2019
DOI: 10.1111/jofi.12751
|View full text |Cite
|
Sign up to set email alerts
|

Political Connections and Allocative Distortions

Abstract: Exploiting a unique institutional setting in Korea, this paper documents that politicians can increase the amount of government resources allocated through their social networks to the benefit of private firms connected to these networks. After winning the election, the new president appoints members of his networks as CEOs of stateowned firms that act as intermediaries in allocating government contracts to private firms. In turn, these state firms allocate significantly more procurement contracts to private f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(105 citation statements)
references
References 77 publications
(65 reference statements)
6
87
0
Order By: Relevance
“…In addition, the model included the size of annual budget expenditure to control for the amount of resources available to each agency. It is possible that the incoming president may have viewed agencies with greater financial resources as being more important, if he or she wanted to control these resources (Schoenherr ). We also added the amount of vertical transfer from central governments, which is a proxy for the degree to which agencies are resource dependent on central governments.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the model included the size of annual budget expenditure to control for the amount of resources available to each agency. It is possible that the incoming president may have viewed agencies with greater financial resources as being more important, if he or she wanted to control these resources (Schoenherr ). We also added the amount of vertical transfer from central governments, which is a proxy for the degree to which agencies are resource dependent on central governments.…”
Section: Methods and Datamentioning
confidence: 99%
“…Because of their critical importance in allocating public resources, the profile of the agency heads has often been the focus of media attention. Previous studies have reported that presidents have often appointed close allies as the executives of these organizations (e.g., Schoenherr ).…”
Section: Institutional Background and Empirical Strategymentioning
confidence: 99%
“…The full set of results are available upon request. of 1 for contracts awarded after a placebo reform on January 1, 2010 32 and include the interaction term Contribute Placebo in my preferred speci cation of equation (1). The coef cient on Contribute Ban remains stable (point estimate of -0.056, a standard error of 0.022), whereas the coef cient on Contribute Placebo is positive, small and not signi cant (point estimate of 0.021, a standard error of 0.029).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Coulomb and Sangnier, 2014), access to credit (Khwaja and Mian, 2005), or procurement contracts' allocation (Goldman et al, 2013;Straub, 2014;Brogaard et al, 2016;Mironov and Zhuravskaya, 2016;Schoenherr, 2018). Even though this literature has established that political connections bene t rms, little is known about how these connections are created and whether they are policy-sensitive.…”
mentioning
confidence: 99%
“…For example, Goldman et al think that if board members of a company have political background, then the company is considered politically connected [31]. Schoenherr believes that a company is considered to have political connections if its CEO is either a graduate from Korea University Business Administration where the then President of South Korea Lee Myung Bak used to study or a former executive of Hyundai Engineering and Construction where Lee used to work [32]. Whereas, Xu et al summarize political connections as the relationship between companies and the government [33].…”
Section: Political Connectionsmentioning
confidence: 99%